The power of close relationships and audiences: Interpersonal closeness and payment observability as determinants of voluntary payments - Elisa Hofmann (Friedrich Schiller University Jena, 2020)
Individual decision-making in Pay-What-You-Want settings is prone to social influence. Es pecially payment observability and the social relationship with other buyers during the payment decision are two important components of social influence. In practical applications of Pay-What-You-Want both phenomena often occur together while not being investigated yet for more than two types of social relationships. Thus, it is not clear how the presence of various types of social relationships influence voluntary payments and how they relate to payment observability. This study examines both drivers of social influence and investigates how payment observability (audience effect) and different types of social relationships (closeness effect) affect voluntary payments at the American Museum of Natural History. 1034 subjects participated in the study. I find that both, payment observability and interpersonal closeness, significantly increase payments. Voluntary payments are significantly higher if observed by other buyers and if visitors are surrounded by interpersonally close others. A high level of consistency between beliefs and behavior with increasing interpersonal closeness is discussed as potential explanation of the closeness effect. The study results are robustly confirmed in a replication study with 995 subjects.
Keywords: C90; D01; D91; L11; 330; social influence; interpersonal closeness; social image concerns; experiments; Pay-What-You-Want